ANATOMICAL PATHOLOGY AND HISTOLOGICAL OF SMALL INTESTINAL ORGANS IN BROILER INFECTED WITH ASCARIDIA GALLI - Rahmawati, Indra; Wardhani, Lailia Dwi Kusuma; Palgunadi, Bagus Uda (The International Journal of Tropical Veterinary and Biomedical Research, 2023)
Infection with Ascaridia galli still attacks poultry farms, especially chickens in Indonesia. This study aims to determine the causes of changes in anatomy pathological and histology in small intestine of broiler. The study was taken from Alif which had clinical symptoms of weakness and anorexia on July 5, 2022 in Gresik Jawa Timur. The results of anatomical pathology and histological examination showed changes in the duodenum and jejunum organs showing hemorrhagic and inflammatory cell infiltration. The results of parasite examination found A.galli worms in the lumen of the small intestine and A.galli worm eggs from feces. In this study, clinical symptoms and anatomy pathological and histology changes of the small intestine in the broiler were caused by infection with A. galli worms.